PENGEMBANGAN MODEL BELAJAR INOVATIF FLIPPED CLASSROOM TERHADAP PENINGKATAN KEMAMPUAN KOGNITIF, AFEKTIF DAN PSIKOMOTOR DALAM MATA KULIAH ASUHAN KEBIDANAN KEHAMILAN - kolifah, kolifah (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2019)
Program Studi D III Kebidanan Stikes Pemkab Jombang Kolifah1, Niken Grah Prihartanti2, Mudhawaroh3 kolifah0607@yahoo.com, nikengrah01@gmail.com, dindhamudha@yahoo.co.id ABSTRACT Weak learning process is one of the problems faced in the world of education. The quality of graduates of health workers is determined by the competence of learners during the education process, the quality of the learning process is needed. Pregnancy midwifery requires skills in the cognitive, affective and psychomotor aspects. The purpose of this study is to improve the cognitive, affective and psychomotor ability of the second semester students of D-III midwifery programme in the course of pregnancy care through the use of innovative learning model Flipped Classroom. This research is a classroom action research through qualitative and quantitative approach. The population in this study is all students of D-III midwifery programme second semester of 40 students. Intruments in this research is written test for cognitive domain, motivation and class observation for affective domain and assessment result of laboratory practice for psychomotor domain. The results showed that there was a significant increase in the results of cognitive domain assessment, there was a significant increase in the results of the assessment of the affective domain and the significant increase in the psychomotor domain after the application of innovative learning methods Flipped Classroom. The result of the application of Flipped Classroom increases students 'attention and confidence in pregnancy care material, it shows the students' learning motivation also increases. Increased motivation is expected to improve student achievement. Keywords: Flipped Classroom, Cognitive, Affective, Psychomotor, Pregnancy care material